Legal Protection for Patients and Health Personnel from an Islamic Legal Perspective - Azzahra Chandra Syafira; Irwansyah Alfaqih; Baharuddin Siregar; Sri Rahayu (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
Health workers are a profession that plays a big role in the health sector. Without us realizing, there are many problems that health workers face when they have to deal with patients. This research reviews "Legal Protection for Patients and Health Workers in the Perspective of Islamic Law". This research aims to find out about the protection of Islamic law in carrying out the task of providing services to patients as medical personnel. The research method uses normative juridical research, which explains a problem and provides a comprehensive, broad assessment from the perspective of Islamic law. This research carries out secondary document studies, through related legislation, books and journals. The data was analyzed qualitatively. The research results show that legal protection for patients must have established rights in order to achieve service standards for medical personnel. Likewise, with legal protection, health workers must have the rights and obligations to serve patients.